Simulasi Sistem Monitoring Pasang Surut Air Laut Dan Peringatan Dini Tsunami Menggunakan Sensor Hc-Sr04: Simulation of Sea Water Tide Monitoring and Tsunami Early Warning System Using HC-SR04 Sensor - Andi Restu; Djul Fikry Budiman; Budi Darmawan (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
The waters in the port of ships often experience slack and there is no adequate tsunami detector. In this thesis, a simulation tool for a tidal monitoring system and an Arduino Uno based tsunami early warning system is designed to measure water levels and send a tsunami early warning automatically via SMS to the user's phonecell. Based on the test results, the average value of the error percentage obtained is 4.49%, this indicates that the system is able to detect the water level quite well. Then in the speed of low tide, the system can detect the difference in the speed of receding water to the number of valves that are open, where when one faucet is opened the average receding speed is 0.077 cm/s, the receding speed when two faucets are opened is 0.1222 cm/s. and the receding speed of the water when the three taps are opened is 0.199 cm/s. Water level data, low tide speed and tsunami status conditions can be saved to a micro SD card in Txt format. And the system is able to send a tsunami early warning via SMS when the system detects the speed of low tide >= 0.18 cm/s.